Dynamic Nuclear Polarization NMR Spectroscopy of Polymeric Carbon Nitride Photocatalysts: Insights into Structural Defects and Reactivity. Issue 23 (8th May 2018) - Li, Xiaobo; Sergeyev, Ivan V.; Aussenac, Fabien; Masters, Anthony F.; Maschmeyer, Thomas; Hook, James M.
Abstract: Metal‐free polymeric carbon nitrides (PCNs) are promising photocatalysts for solar hydrogen production, but their structure–photoactivity relationship remains elusive. Two PCNs were characterized by dynamic‐nuclear‐polarization‐enhanced solid‐state NMR spectroscopy, which circumvented the need for specific labeling with either 13 C‐ or 15 N‐enriched precursors. Rapid 1D and 2D data acquisition was possible, providing insights into the structural contrasts between the PCNs. Compared to PCN_B with lower performance, PCN_P is a more porous and more active photocatalyst that is richer in terminal N−H bonds not associated with interpolymer chains. It is proposed that terminal N−H groups act as efficient carrier traps and reaction sites. Abstract : Generous to a fault : Structural defects in photocatalytic polymeric carbon nitrides are correlated with photocatalyzed hydrogen evolution. An increased number of terminal N−H bonds (▪(blue)) and reduced hydrogen bonding is associated with high performance, whereas polymer containing fewer terminal N−H bonds () solicits lower performance.